Practice and Outcome of Umbilical Cord Care among Recently-Delivered Mothers Attending Postnatal Clinics in Ibadan, Nigeria (African Journal of Biomedical Research, 2023)
One of the main causes of neonatal deaths, particularly in low- and middle-income nations, has been identified as umbilical cord infection. In the first four weeks of life, 4 million (3.1 percent) of the 130 million babies born worldwide each year die. Due to their high susceptibility to infections, newborns' umbilical cord care requires extra care in order to reduce neonatal fatalities. This study aims to evaluate the knowledge and practice of umbilical cord care as well as the results of the care among recently delivered mothers visiting postnatal clinics in Ibadan, Nigeria. The three hospitals chosen for this cross-sectional study represent Nigeria's three levels of healthcare institutions. The enrolment of study participants used a simple random sampling technique. Data were gathered using a self-structured questionnaire with a reliability rating of 0.76. Utilizing SPSS version 20 for data analysis, chi-square was used to test the hypothesis at the 0.05 level of significance.Results from the study showed that only 34.7% of the mothers who had just given birth had good knowledge of umbilical cord care, while 55.3% had good practice. Only 5.3% of the mothers reported negative outcome while caring the for umbilical cord at home. Fever (3.4 percent), yellowish discharge from the umbilical cord (1.5 percent), reddish skin directly beneath the cord (1.4 percent), discomfort near the umbilical stump (1.4 percent), and foul-smelling cord are some of the negative outcomes that mothers have reported (0.7 percent ).A total number of 58.1% of the mothers reported that the umbilical stump detachment lasted 5-15 days, while 38.1% of them reported that navel healing lasted for 4-6 weeks. A significant association was found between monthly income and materials used for umbilical cord care after delivery (χ2=18.467, df=6, p=0.005)Many recently-delivered mothers lack adequate knowledge of umbilical cord care, yet, most of them had good umbilical cord care practices because they delivered their babies in the hospital. There is report of negative outcome of umbilical cord care, though very few, this is detrimental to the survival of the new-borns. Mothers’ economic status is associated with the materials used for umbilical cord care, which consequently determines the outcome of the cord care practices.